Management of extracted human teeth by dental students in East Coastal Region of India - Parveen Sultana Shaik; Suresh Chand Yaddanapalli; Srinivas Ravoori; Srinivas Pachava; Asha Lodagala; Nijampatnam P. M. Pavani (Wolters Kluwer Medknow Publications, 2021)
Background: Dental students practice on extracted human teeth (EHT) in their preclinical to learn professional and technical skills before performing dental procedures on patients. Aim: The aim of the present investigation was to assess the management of EHT among dental students in the east coastal region of India. Materials and Methods: A cross-sectional study was conducted on II, III, and IV Bachelor of Dental Surgery (BDS) students from five dental colleges in India's east coastal region, which were chosen using the fishbowl technique. Data was collected using a pretested, validated self-administered questionnaire and analysed using the Chi-square test, Mann-Whitney test, Kruskal-Wallis test, and linear regression. Results: A total of 649 students participated from five dental colleges, among them, 43.6% (283) were II BDS, 29.6% (192) were III BDS, and 26.8% (174) were IV BDS. About 66% of the participants do not know that the EHT are a source of infection; 22% of them noted that there was an incidence of infection with the use of EHT; 81.5% do not know that guidelines have to be given by the regulatory body/institution to handle EHT. Only 2% of the people think it was necessary to disinfect/sterilize EHT before use, while 33% of the study population felt that there was a need to wear mouth masks and gloves while working on EHT. In the study group, only 43% know that formalin was used as a storage/disinfecting medium for EHT and 80% of them experienced hazards due to chemicals used for storage/disinfecting medium of EHT. Conclusion: The results of this investigation stipulated that awareness, attitude, and practices of undergraduate students in relation to the handling of EHT were poor. However, deficiencies were observed in relation to teaching the materials and methods suitable for the management of EHT which reveals the need to incorporate the guidelines in their curriculum.